Rationale for and Methods of Superiority, Noninferiority, or Equivalence Designs in Orthopaedic, Controlled Trials - Vavken, Patrick (Springer-Verlag, 2011)
BACKGROUND: To provide value-based healthcare in orthopaedics, controlled trials are needed to assess the comparative effectiveness of treatments. Typically comparative trials are based on superiority testing using statistical tests that produce a p value. However, as orthopaedic treatments continue to improve, superiority becomes more difficult to show and, perhaps, less important as margins of improvement shrink to clinically irrelevant levels. Alternative methods to compare groups in controlled trials are noninferiority and equivalence. It is important to equip the reader of the orthopaedic literature with the knowledge to understand and critically evaluate the methods and findings of trials attempting to establish superiority, noninferiority, and equivalence. QUESTIONS/PURPOSES: I will discuss supplemental and alternative methods to superiority for assessment of the outcome of controlled trials in the context of diminishing returns on new therapies over old ones. METHODS: The three methods—superiority, noninferiority, and equivalence—are presented and compared, with a discussion of implied pitfalls and problems. RESULTS: Noninferiority and equivalence offer alternatives to superiority testing and allow one to judge whether a new treatment is no worse (within a margin) or substantively the same as an active control. Noninferiority testing also allows for inclusion of superiority testing in the same study without the need for adjustment of the statistical methods. CONCLUSIONS: Noninferiority and equivalence testing might prove most valuable in orthopaedic, controlled trials as they allow for comparative assessment of treatments with similar primary end points but potentially important differences in secondary outcomes, safety profiles, and cost-effectiveness.